PENGARUH PENGALAMAN KERJA DAN TINGKAT PENDIDIKAN TERHADAP KINERJA PEGAWAI DAN TUNJANGAN KINERJA SEBAGAI VARIABEL INTERVENING - Jumawan Jumawan (STIE Mahardhika, 2021)
The purpose of this study was to determine the direct and indirect effect of work experience variables and education level on performance benefits and employee performance. The population in this study were 248 employees at one of the Customs and Excise Offices in the Bekasi area. Based on the Slovin formula, the sample size of this study was 71 respondents. Sampling with probability sampling techniques, using simple random sampling method. Meanwhile, data analysis uses Path Analysis. Based on the research results, it shows that: work experience (X1) and education level (X2) have a direct and significant effect on performance allowance (Z). Work experience (X1) and education level (X2) have a direct and significant effect on employee performance (Y). And the performance allowance (Z) has a direct and significant effect on employee performance (Y).